Educational Strategy in Preserving and Developing Malay Islamic Arts and Culture - Sufia, Neng; Riadi, Haris; Erlina, Gusti; Rahmad, Rahmad (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is motivated by concerns over the diminishing existence of Malay Islamic arts and culture amid globalization and the lack of appreciation from the younger generation. The main objective of this study is to formulate strategies for preserving Malay Islamic cultural arts so that they remain relevant in the modern era. This study employs a qualitative approach using a literature review method. Data were collected from various written sources and analyzed through content analysis to identify applicable preservation strategies. The results of the study reveal six main strategies: education and socialization, cultural festivals, digital documentation, artist development, cultural filtering, and the use of social media. Collaboration among academics, the government, and the community is key to successful preservation. These findings indicate that the preservation of Malay Islamic cultural arts requires an adaptive approach based on local wisdom and digital technology, which can enhance cultural awareness and strengthen the identity of the younger generation amid the challenges of globalization.